A New Method for Determining the Optical Constants of Highly Transparent Solids. Issue 1 (January 2017) - Li, Xingcan; Wang, Chengchao; Zhao, Junming; Liu, Linhua
Highly transparent substrates are of interest for a variety of applications, but it is difficult to measure their optical constants precisely, especially the absorption index in the transparent spectral region. In this paper, a combination technique (DOPTM-EM) using both the double optical pathlength transmission method (DOPTM) and the ellipsometry method (EM) is presented to obtain the optical constants of highly transparent substrates, which overcomes the deficiencies of both the two methods. The EM cannot give accurate result of optical constants when the absorption index is very weak. The DOPTM is suitable to retrieve the weak absorption index; however, two sets of solutions exist for the retrieved refractive index and absorption index, and only one is the true value that needs to be identified. In the DOPTM-EM, the optical constants are measured first by using the EM and set as the initial value in the gradient-based inverse method used in the DOPTM, which ensures only the true optical constants are retrieved. The new method simultaneously obtains the refractive index and the absorption index of highly transparent substrate without relying on the Kramers–Kronig relation. The optical constants of three highly transparent substrates (polycrystalline BaF2, CaF2, and MgF2 ) were experimentally determined within wavelength range from ultraviolet to infrared regions (0.2–14 µm). The presented method will facilitate the measurement of optical constants for highly transparent materials.